NRF2 Knockdown Resensitizes 5-Fluorouracil-Resistant Pancreatic Cancer Cells by Suppressing HO-1 and ABCG2 Expression - Kim, Eui Joo (Int J Mol Sci, 2020)
Chemoresistance is a leading cause of morbidity and mortality in patients with pancreatic cancer and remains an obstacle to successful treatment. The antioxidant transcription factor nuclear factor (erythroid-derived 2)-related factor 2 (NRF2), which plays important roles in tumor angiogenesis and invasiveness, is upregulated in pancreatic ductal adenocarcinoma (PDAC), where it correlates with poor survival. Here, we investigated the role of NRF2 in two 5-Fluourouracil-resistant (5-FUR) PDAC cell lines: BxPC-3 and CFPAC-1. Levels of NRF2 and antioxidants, such as heme oxygenase 1 (HO-1), NAD(P)H quinone dehydrogenase 1 (NQO1), and superoxide dismutase 2 (SOD2), were higher in the chemoresistant cells than in their chemosensitive counterparts. Expression of epithelial mesenchymal transition (EMT) markers, stemness markers, including Nanog, Oct4, and CD133, and that of the drug transporter ATP binding cassette, subfamily G, member A2 (ABCG2) was also upregulated in 5-FUR PDAC cells. NRF2 knockdown reversed 5-FU resistance of PDAC cells via suppression of ABCG2 and HO-1. In summary, these data indicate that NRF2 is a potential target for resensitizing 5-FUR PDAC cells to 5-FU to improve treatment outcomes in patients with pancreatic cancer.